The role of CD68+ macrophage in classical Hodgkin lymphoma patients from Egypt - Osama Mohamed; Ahmed El Bastawisy; Nasr Allahlobi; Mona S. Abdellateif; Abdel Rahman N. Zekri; Sabry Shaarawy; Zeinab Korany; Marwa Mohanad; Abeer A. Bahnassy (BMC, 2020)
Abstract Background CD68+ tumor-associated macrophages (TAM) play an important role in the progression of classical Hodgkin lymphoma (cHL). We assessed the role of CD20 and CD68 + TAM in a cohort of cHL patients from Egypt and correlated the number of CD68 + cells with patients' characteristics, response to treatment, overall and progression free survival rates (OS & PFS). Methods CD20 expression and CD68 + TAM numbers were assessed in representative tumor tissues obtained from 81 cHL patients using flowcytometry (FCM), immunohistochemistry (IHC), and Rt-PCR techniques. Results The expression levels of CD68 protein by IHC was high in 27 (33.3%), moderate in 15 (18.5%), low in 15 (18.5%), and negative in 24 (29.6%) patients (p = 0.13). CD68-mRNA expression was high in 43/81(53.1%), and low in 38(46.9%) patients (p = 0.6). The number of CD68 + TAM (by FCM) was low (< 20 cells) in 42/81 (51.9%), and high (≥20 cells) in 39/81 (48.1%) patients (p = 0.74). CD68 expression (by FCM, IHC& Rt-PCR) associated significantly with poor response to treatment, decreased CD20 expression, reduced OS and PFS rates (p < 0.001 for all). CD68 expression (by Rt-PCR only) associated significantly with advanced disease stage (p = 0.04). The age of the patients, high CD20 expression & high CD68+ macrophage number were independent prognostic factors for OS (p= 0.02, p = 0.008 & p = 0.009; respectively). However, the age of the patient, high CD20, and high CD68+ macrophage expression (by FCM&IHC) were independent prognostic factors for DFS (p. = 0.004, p. = 0.01, p. = 0.007 and p. = 0.01; respectively). Conclusion CD68 + TAM expression (by Rt-PCR, FCM and/or IHC) can identify patients with poor response to treatment and reduced survival rates (OS& PFS). Assessment of CD68 + positive macrophages by FCM is superior to other methods (Rt-PCR and IHC) as a prognostic factor for DFS and OS rates.